A non-radial approach to improve the interval cost efficiency score in DEA. (14th October 2021) - Tohidi, Ghasem; Tohidnia, Simin
This paper suggests an approach for improving the cost efficiency score of inefficient decision making units (DMUs) with interval data. Corresponding to each inefficient DMU, we consider an interval ideal input vector and then develop two non-radial models to determine a point in the production possibility set that can produce the given interval output vector with the minimum possible cost and is closest point to the corresponding ideal point. By replacing the observed interval input vector with the interval input vector of the obtained point, one can improve the lower bound of the interval cost efficiency score as much as possible while the upper bound can achieve one. A numerical example also will be designed to demonstrate the applicability of the proposed approach.